PERANCANGAN PRODUK CONVERTIBLE BAG DENGAN PANEL SURYA YANG ERGONOMIS MENGGUNAKAN METODE QUALITY FUNCTION DEPLOYMENT (QFD): Indonesia - R A Atha Nabilla Rahmi Atha; Mochamad Tutuk Safirin (J-ENSITEC, 2022)
Technological advances in the field of Transportation, a socio-cultural truth that occurs in the community, that today the internet greatly affects citizens in undergoing activities in the community. The number of users of smart phones or smartphones, both on android and iOS systems makes people dependent on smartphones and the internet. Online motorcycle taxi drivers are required to have a mobile phone that can function properly and can be used throughout the day or during his work. This requires online motorcycle taxi drivers to bring their mobile phone cables and Chargers in order to continue receiving orders. Based on the above, there is an opportunity to make a convertible bag equipped with solar panels using the Quality Function Deployment (QFD) method. This study uses experimental methods. This study found that the final specifications of the bag are cheap, there are charging features, easy to store, convenient to use, have a large enough size, have good quality, and design that consumers want. Solar panels can charge a battery of 5,600 mah for one hour in bright sunlight conditions, with this figure can charge mobile phone batteries in general from 0% -100% less than 1 hour